Materialism in early and modern pentecostal movements in Nigeria (2013)
The emergence of Pentecostal movements within the landscape of Nigeria was characterized with emphasis on second birth, holiness, sanctification, indwelling of the Holy Spirit and possession of the nine gifts of the Holy Spirit by a Christian. This way of life was not only verbalized but adequately demonstrated by the Early Pentecostal leaders. Conversely, there are sufficient evidences that there is a change in focus by modern Pentecostals from holiness messages to “prosperity ” message. This trend has affected their psyche to the extent that most Pentecostal preachers in Nigeria seem to be driven by the quest for materialism; a situation that negates the original Pentecostal ideals and principles. Therefore the aim of this paper is to articulate in strong terms the deviation of the modern Pentecostals and to suggest a revisit of the biblical principles imbibed by the early Pentecostals.